Criminological Analysis of Sexual Violence against Children in Mamasa - Pasande, Jhon Franklin; Purwanda, Sunardi; Sabir, Muhammad; Tijjang, Bakhtiar; Kairuddin, Kairuddin (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study aims to observe and pay attention to the applicable legal norms in relation to the facts regarding the application of criminal penalties for perpetrators of child sexual intercourse in Mamasa, This study uses a sociological or empirical approach in Mamasa Regency. Types and sources of legal materials use primary and secondary legal materials, The factors causing the crime of sexual intercourse with children in Mamasa are low levels of education, the economy in this case poverty and environmental factors that can have major influences on a person's treatment. To prevent sexual intercourse with children, preventive efforts are needed such as preemptive, namely prevention so that the crime does not occur, then preventive efforts, namely action taken by authorized officers in accordance with laws and regulations, and repressive efforts, namely efforts to return perpetrators of crimes to further return perpetrators who have served their sentences to be able to return to community life.